2015
DOI: 10.1161/strokeaha.114.008484
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Neuroprotection Is Associated With Recovery of Spectral Edge Frequency After Asphyxia in Preterm Fetal Sheep

Abstract: At 103 to 104 days gestation, fetuses were randomly assigned to sham occlusion followed by normothermia (sham-normothermia, n=8), or whole-body cooling for 72 hours (sham-hypothermia, n=8), or umbilical cord occlusion for 25 minutes, followed by sham hypothermia (occlusion-normothermia, n=12), or whole-body cooling started from 30 minutes (occlusion-early hypothermia, n=10), or 5 hours (occlusion-delayed hypothermia, n=7) after occlusion and continued for 72 hours. Mild whole-body cooling was induced by circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Takada model causes a noninvasive global asphyxia extra-uterus in a very immature brain (P1-P2 rats), which resembles the human condition experienced by premature neonates (Semple, Blomgren et al 2013;Takada, dos Santos Haemmerle et al 2015). In other species, perinatal hypoxia-ischemia has been used in sheeps (Williams, Gunn et al 1990;Bennet, Quaedackers et al 2000;Bennet, Roelfsema et al 2007;Wassink, Barrett et al 2015) and in rabbits (Derrick, Luo et al 2004;Tan, Drobyshevsky et al 2005), in which kits present cerebral palsy phenotype with limbs hypertonia.…”
Section: Introductionmentioning
confidence: 99%
“…Takada model causes a noninvasive global asphyxia extra-uterus in a very immature brain (P1-P2 rats), which resembles the human condition experienced by premature neonates (Semple, Blomgren et al 2013;Takada, dos Santos Haemmerle et al 2015). In other species, perinatal hypoxia-ischemia has been used in sheeps (Williams, Gunn et al 1990;Bennet, Quaedackers et al 2000;Bennet, Roelfsema et al 2007;Wassink, Barrett et al 2015) and in rabbits (Derrick, Luo et al 2004;Tan, Drobyshevsky et al 2005), in which kits present cerebral palsy phenotype with limbs hypertonia.…”
Section: Introductionmentioning
confidence: 99%
“…Although hypothermia is not used clinically for treatment of preterm infants, in preclinical studies using the same protocol as the present study, prolonged cerebral hypothermia started at 30 or 90 minutes after UCO was highly protective, 47,48 whereas white and gray matter protection was largely lost when initiation of hypothermia was delayed for 5 hours. 48 The finding that delaying hAEC administration until 24 hours after UCO, at a time when the secondary deterioration of mitochondrial function is well established in this model, 25 This finding is consistent with recent studies in fetal sheep of administration of mesenchymal stromal cell-derived extracellular vesicles 53 and MSCs after asphyxia. 54 The mechanisms of this EEG suppression by hAECs between seizures are unknown, but likely multifactorial and may include reduced inflammation, and an altered balance between inhibitory and excitatory neurotransmitters and neuromodulators, and suppression of metabolism.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies suggest that optimal recovery of cerebral metabolism after such severe HI is only present for the first few hours 6 , 7 . Pre-clinical studies in term-equivalent animals have shown that therapeutic hypothermia could prevent the majority of cell death when started within 3 hours after HI 45 , but hypothermic neuroprotection was largely lost if the start time of treatment was delayed until after ~6 hours 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic hypothermia after HI is neuroprotective in both preterm and term animals 7 , 8 , and is now standard care for term newborns after moderate to severe HI 9 . Hypothermia, and potentially other treatments that act through similar pathways, is only effective when started during the latent phase after HI; efficacy is rapidly lost with increasing delay after HI as previously reviewed 3 .…”
Section: Introductionmentioning
confidence: 99%